A universal multi-additive strategy to enhance efficiency and stability in inverted perovskite solar cells. (May 2023) - Castriotta, Luigi Angelo; Calabrò, Emanuele; Di Giacomo, Francesco; Reddy, Sathy Harshavardhan; Takhellambam, Daimiota; Paci, Barbara; Generosi, Amanda; Serenelli, Luca; Menchini, Francesca; Martini, Luca; Tucci, Mario; Di Carlo, Aldo
Abstract: Perovskite solar technology has become a trend topic in the last decade, reaching promising efficiencies up to 25.7 %. Researchers mainly focused on obtaining high performance rather than caring for stability under accelerated stress conditions, such as thermal and light soaking tests. For this reason, we studied a standard triple cation perovskite (∼1.58 eV) and wider bandgap perovskite (∼1.63 eV) with the scope of finding a common strategy to build a robust device stable over time independently of the perovskite used. We use a combination of additives inside the perovskite ink: ionic liquid 1-Butyl-3-methylimidazolium tetrafluoroborate (BMIM-BF4), alkylamine ligands oleylamine (OAm) and benzylhydrazine hydrochloride (BHC). Our work reveals that the combination of these additives helps to improve the efficiency and stability of the entire device, reaching a power conversion efficiency up to 21.3 % and over 20 % for both types of perovskite and stability beyond 1000 h under continuous light soaking. The universal applicability of this method was further applied to a robust methylammonium free perovskite, leading to an impressive stability both under light soaking and under 85 °C, showing T90 > 1500 h and T80 > 8658 h, respectively: the solar cells modified with the additive mixture retained 95 % of their efficiency after 1000 h under light soaking at 45 °C and 100 % of their efficiency after 1500 h of stress at 85 °C. Graphical Abstract: ga1 Highlights: A universal approach to enhance performances and stability of inverted PSCs by introducing a combination of additives. 3 types of Perovskite were tested, improving their performances from 14.9 % to up to 21.30 % efficiency. ISOS L-1 and ISOS T-1 reached a T90 > 1500 h and a T80 > 8650 h, respectively.